Measuring the Preference of the College in Pokhara: A Multidimensional Scaling Approach - Gupta, Sweta Kumari; Palikhe, Amin (Kanya Journal, 2024)
The multidimensional scaling approach is the process of mapping the position of object in a perpetual space. Therefore, the purpose of this study was to mapping the measuring of preferences of colleges in Pokhara by using multidimensional scaling approach. The four QAA (Quality Assurance Accreditation) register college under University Grants Commission, Nepal was taken as a sample of the study in the Pokhara valley. It has used multistage sampling procedures. The study has purposefully taken convenience sampling procedure by taking 162 samples from preferential, similarities and dissimilarities questionnaires distributed from 20 July, 2023 and collected on 21 August, 2023 via messenger group and personal mail. Therefore, the descriptive research design has been used. The data was processed and analysised through Excel and SPSS 20 version by using dissimilarities based non attribute method under multidimensional scaling approach through measuring Stress value, R-square value and spatial mapping. The result shows that Prithvi Narayan Campus (PNC) is the most preferred college in Pokhara and it is quite similar with Gupteshwor Multiple Campus (GMC) in terms of operational activity. In terms of infrastructure and facilities, Kanya Campus (KC) and Kalika Multiple Campus (KMC) look similar. Where, Janapruya Multiple Campus (JMC) is distinct among the other colleges. Since a lot of colleges and university in the education sector are establishing these days, this paper probably be helpful in making positioning strategy on this sector as well its implication be beneficial to various stakeholders. Therefore, it will be more significant to focus on the attribute base MSD to measure the perpetual mapping in the field of marketing, finance as well as profit and nonprofit making institution in Pokhara valley.